Resin composition, prepreg, and fiber-reinforced plastic
Patent Information
- Application Number
- JP2024208587
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-03-15
- Filing Date
- 2024-11-29
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2042-03-14
AI Technical Summary
【0016】 本発明によれば、靭性および弾性率に優れた硬化物および繊維強化プラスチックを提供することができる。
Smart Images

Figure 2025023129000007 
Figure 2025023129000001 
Figure 2025023129000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a curable resin composition, and a film, a molded article, a prepreg, and a fiber-reinforced plastic using the same, which are suitable for use in sports and leisure applications, general industrial applications, aircraft material applications, etc. This application claims priority based on Japanese Patent Application No. 2021-041609, filed on March 15, 2021, the contents of which are incorporated herein by reference. [Background technology]
[0002] Fiber-reinforced plastics, which are one type of fiber-reinforced composite material, are lightweight, strong, and rigid, and therefore are widely used in a wide range of applications, from sports and leisure to industrial applications such as automobiles and aircraft. One method for manufacturing fiber-reinforced plastics is to use an intermediate material, i.e., prepreg, in which a matrix resin is impregnated into a reinforcing material made of long fibers (continuous fibers) such as reinforcing fibers. This method has the advantage that it is easy to control the content of reinforcing fibers in fiber-reinforced plastics and that it is possible to design the content to be high. A molded product can be obtained by stacking multiple prepregs and heat-curing them.
[0003] Due to the need for weight reduction, carbon fibers with excellent specific strength and specific modulus are used as reinforcing fibers, and epoxy resins with excellent adhesion to the carbon fibers are often used as matrix resins. However, epoxy resins generally tend to be brittle and have low toughness when cured. Therefore, improving the toughness of epoxy resins has been a technical challenge in order to improve the fracture toughness and rigidity of fiber-reinforced plastics. In the past, epoxy resins have been toughened by modification methods using engineering plastics such as polyethersulfone. In recent years, studies have been conducted to improve toughness by adding modifiers such as block copolymers and using the phase separation structure that occurs during the resin curing process. However, in any of these methods, the glass transition temperature (Tg) and modulus of elasticity of the cured product tend to decrease, and a significant increase in viscosity due to the addition of polymers is unavoidable.
[0004] To solve these problems, attempts have been made to polymerize the monomer that is the basis of the modifier in a system using an "in situ polymerization method," and to simultaneously generate the modifier and perform the curing reaction of the epoxy resin (Non-Patent Document 1). In this attempt, a vinyl polymer generated by radical polymerization is used as the modifier, and in the field of fiber-reinforced plastics, technological development is underway to manufacture intermediate materials by combining epoxy resins with radically polymerizable monomers (Patent Documents 1 to 3). [Prior art documents] [Non-patent literature]
[0005] [Non-Patent Document 1] Toshiyuki Oyama, Network Polymer 36 211 (2015) [Patent documents]
[0006] [Patent Document 1] Patent No. 3669090 [Patent Document 2] Japanese Patent Application Publication No. 11-43547 [Patent Document 3] Patent No. 5424021 Summary of the Invention [Problem to be solved by the invention]
[0007] One object of the present invention is to provide a prepreg that has excellent toughness and elastic modulus when cured to form a cured product. Another object of the present invention is to provide a prepreg that is capable of forming a phase-separated structure of a matrix resin that can improve toughness when cured to form a cured product. [Means for solving the problem]
[0008] The present invention has the following aspects [1] to
[52] . [1] A prepreg including carbon fibers and a matrix resin, the matrix resin including an epoxy resin, a curing agent, a monofunctional (meth)acrylate monomer having a molecular weight of 200 or more, and a polyfunctional (meth)acrylate monomer. [2] The prepreg according to [1], wherein the curing agent contains component (b1) which is at least one selected from the group consisting of dicyandiamide, ureas, imidazoles, and aromatic amines. [3] The prepreg according to [2], wherein the curing agent contains dicyandiamide. [4] The prepreg according to any one of [1] to [3], wherein the curing agent contains at least one kind of radical polymerization initiator, component (b2). [5] The prepreg according to [4], wherein the component (b2) contains at least one peroxide-based compound selected from the group consisting of diacyl peroxides, alkyl peroxy esters, peroxydicarbonates, peroxyketals, dialkyl peroxides, and hydroperoxides. [6] The prepreg according to any one of [1] to [5], wherein the content of the polyfunctional (meth)acrylate monomer in the prepreg is greater than the content of the monofunctional (meth)acrylate monomer having a molecular weight of 200 or more. [7] The prepreg according to any one of [1] to [6], wherein the monofunctional (meth)acrylate monomer having a molecular weight of 200 or more includes at least one monomer selected from isobornyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, phenoxyethyl (meth)acrylate, dicyclopentenyl (meth)acrylate, and dicyclopentanyl (meth)acrylate. [8] The prepreg according to any one of [1] to [7], wherein the polyfunctional (meth)acrylate monomer comprises an acrylate monomer represented by the following structural formula (1):
[0009] [ka]
[0010] (In formula (1), each X independently represents ethylene oxide or propylene oxide, each n, m, and l independently represents an integer of 0 to 10, and Y independently represents an acryloyl group or a hydrogen atom.) [9] The prepreg according to any one of [1] to [8], comprising 5 to 45 parts by mass of the monofunctional (meth)acrylate monomer having a molecular weight of 200 or more and the polyfunctional (meth)acrylate monomer relative to 100 parts by mass of the total epoxy resin.
[10] A prepreg comprising reinforcing fibers and a matrix resin, the matrix resin comprising an epoxy resin, and a cured product obtained by curing the matrix resin under the following curing conditions has a sea-island phase-separated structure composed of domains X and Y, the domains X constitute islands having a size R of 400 nm or less as measured by the following measurement method, and the ratio L / R of the distance L between the domains X to the size R is 1.1 or more. Curing conditions; The matrix resin is injected between two glass plates to form a plate of 2 mm thickness, and the oven atmosphere temperature is raised to 130°C at a rate of 2°C / min and maintained at 130°C for 90 minutes. Measurement conditions; As a pretreatment, a section of 60 to 90 nm thick is cut from the cross section of the cured material using an ultramicrotome, and the obtained section is exposed to RuO4 vapor for 7 minutes to perform electronic staining. Alternatively, a section of 60 to 90 nm thick is cut from the cross section of the cured material that has been previously exposed to OsO4 vapor for 16 hours using an ultramicrotome. The phase separation structure of the section that has been electronically stained by pretreatment is observed using a transmission electron microscope (TEM) with the acceleration voltage set to 80 kV, and a TEM image is obtained. The obtained TEM image is smoothed and background subtracted using image analysis software, and the boundary of the binarized image is detected. The size R is the median of the maximum Feret's diameter of the domain X. The distance L between domains X is the median of the distance from the center of gravity of domain X to the center of gravity of another domain X that is closest to the domain X.
[11] The prepreg according to
[10] , wherein the ratio L / R is 100 or less.
[12] The prepreg according to
[10] or
[11] , wherein the size R is 1 nm or more.
[13] The prepreg according to any one of
[10] to
[12] , wherein the matrix resin contains the following components (A) and (B): Component (A): (Meth)acrylate monomer Component (B): Hardener.
[14] The prepreg according to
[13] , wherein the component (A) contains a monofunctional (meth)acrylate monomer.
[15] The prepreg according to
[13] or
[14] , wherein the component (A) contains a polyfunctional (meth)acrylate monomer.
[16] The prepreg according to any one of
[10] to
[15] , wherein the domain X contains a polymer of a (meth)acrylate monomer.
[17] The prepreg according to any one of
[10] to
[16] , wherein the domain Y contains a cured product of an epoxy resin.
[18] The prepreg according to any one of
[13] to
[17] , wherein the component (B) contains a component (b1) which is at least one selected from the group consisting of dicyandiamide, ureas, imidazoles, and aromatic amines.
[19] The prepreg according to
[18] , wherein the component (b1) is contained in an amount of 1 to 15 parts by mass per 100 parts by mass of the total epoxy resin contained in the matrix resin.
[20] The prepreg according to any one of
[13] to
[19] , wherein the component (B) contains at least one kind of component (b2) which is a radical polymerization initiator.
[21] The prepreg according to
[20] , wherein the component (b2) is contained in an amount of 0.1 to 5 parts by mass per 100 parts by mass of the total matrix resin.
[22] The prepreg according to
[20] or
[21] , wherein the component (b2) contains a compound having a 10-hour half-life temperature of 70°C or higher.
[23] The prepreg according to any one of
[20] to
[22] , wherein the component (b2) contains at least one peroxide-based compound selected from the group consisting of diacyl peroxides, alkyl peroxy esters, peroxydicarbonates, peroxyketals, dialkyl peroxides, and hydroperoxides.
[24] The prepreg according to any one of
[10] to
[23] , wherein the component (A) is contained in an amount of 5 to 45 parts by mass per 100 parts by mass of the total epoxy resin.
[25] The prepreg according to any one of
[10] to
[24] , wherein the reinforcing fibers include carbon fibers.
[26] A fiber-reinforced plastic obtained by curing the prepreg according to any one of
[10] to
[25] .
[27] A fiber-reinforced plastic comprising reinforcing fibers and a matrix resin, wherein the matrix resin has a sea-island phase-separated structure consisting of domains X and Y, wherein the domains X constitute islands having a size R of 400 nm or less as measured by the following measurement method, and wherein the ratio L / R of the distance L between domains X to the size R is 1.1 or more. Measurement conditions; As a pretreatment, the cross section of the fiber-reinforced plastic is mechanically polished to obtain a mirror surface. The resulting smooth cross section is then exposed to RuO4 vapor or OsO4 vapor for electronic staining. After conducting a conductive treatment, a scanning electron microscope (SEM) with an accelerating voltage set to 5 kV is used to obtain a backscattered electron image of the electronically stained cross section, and the phase separation structure is observed. The backscattered electron image obtained is smoothed and background subtracted using image analysis software, after which the boundaries of the binarized image are detected. The size R is the median of the maximum Feret's diameter of the domain X. The distance L between domains X is the median of the distance from the center of gravity of domain X to the center of gravity of the nearest other domain X.
[28] The fiber-reinforced plastic according to
[27] , wherein the ratio L / R is 100 or less.
[29] The fiber-reinforced plastic according to
[27] or
[28] , wherein the size R is 1 nm or more.
[30] The fiber-reinforced plastic according to any one of
[27] to
[29] , wherein the domain X contains a polymer of a (meth)acrylate monomer.
[31] The fiber-reinforced plastic according to any one of
[27] to
[30] , wherein the domain Y contains a cured product of an epoxy resin.
[32] The fiber-reinforced plastic according to any one of
[27] to
[31] , wherein the reinforcing fibers include carbon fibers.
[34] The prepreg according to any one of [1] to
[25] , wherein a cured product obtained by curing the matrix resin under the following curing conditions has a sea-island phase-separated structure composed of domains X and Y, the domains X forming islands each having a size R of 400 nm or less as measured by the following measurement method, and a ratio L / R of the distance L between the domains X to the size R is preferably 1.1 or more and 100 or less, more preferably 1.1 or more and 50 or less, even more preferably 1.25 or more and 10 or less, and particularly preferably 1.5 or more and 5.0 or less.
[35] The prepreg according to any one of [1] to
[25] and
[34] , wherein the matrix resin contains an epoxy resin and a (meth)acrylate monomer, and the content of the (meth)acrylate monomer is preferably 5 parts by mass or more and 45 parts by mass or less, and more preferably 10 parts by mass or more and 40 parts by mass or less, relative to 100 parts by mass of all epoxy resins in the prepreg.
[36] The prepreg according to any one of [1] to
[25] and
[34] to
[35] , wherein the matrix resin contains an epoxy resin and a component (b1) that hardens the epoxy resin, and the content of the component (b1) is preferably 1 part by mass or more and 15 parts by mass or less, and more preferably 2 parts by mass or more and 12 parts by mass or less, relative to 100 parts by mass of all the epoxy resins contained in the matrix resin.
[37] The prepreg according to any one of [1] to
[25] and
[34] to
[36] , wherein the matrix resin contains an epoxy resin and dicyandiamide, and the content of dicyandiamide is preferably 1 to 15 parts by mass, and more preferably 2 to 10 parts by mass, per 100 parts by mass of the total epoxy resin contained in the matrix resin.
[38] The prepreg according to any one of [1] to
[25] and
[34] to
[37] , wherein the matrix resin contains a (meth)acrylate monomer and a component (b2) that cures the (meth)acrylate monomer, and the content of component (b2) is preferably 0.1 part by mass or more, and more preferably 0.2 part by mass or more, per 100 parts by mass of the total matrix resin.
[39] The prepreg according to any one of [1] to
[25] and
[34] to
[38] , wherein the matrix resin contains a liquid epoxy resin, and the viscosity of the liquid epoxy resin at 25°C is preferably 0.1 Pa s or more and 500 Pa s or less, and more preferably 0.1 Pa s or more and 300 Pa s or less.
[40] The prepreg according to any one of [1] to
[25] and
[34] to
[39] , wherein the matrix resin contains an epoxy resin, and the content of the epoxy resin is preferably 70 parts by mass or more and less than 100 parts by mass, and more preferably 80 parts by mass or more and 95 parts by mass or less, per 100 parts by mass of the matrix resin.
[41] The prepreg according to any one of [1] to
[25] and
[34] to
[40] , wherein the matrix resin contains a liquid epoxy resin, and the content of the liquid epoxy resin is preferably 20 parts by mass or more and 80 parts by mass or less, more preferably 20 parts by mass or more and 75 parts by mass or less, even more preferably 25 parts by mass or more and 70 parts by mass or less, and particularly preferably 28 parts by mass or more and 50 parts by mass or less, relative to 100 parts by mass of all epoxy resins contained in the epoxy resin composition.
[43] The prepreg according to any one of [1] to
[25] and
[34] to
[42] , wherein the matrix resin contains a solid epoxy resin, and the content of the solid epoxy resin is preferably 10 parts by mass or more and 80 parts by mass or less, more preferably 13 parts by mass or more and 70 parts by mass or less, and even more preferably 15 parts by mass or more and 60 parts by mass or less, relative to 100 parts by mass of all epoxy resins contained in the epoxy resin composition.
[44] The prepreg according to any one of [1] to
[25] and
[34] to
[43] , wherein the matrix resin contains an epoxy resin and a thermoplastic resin, and the content of the thermoplastic resin is preferably from 1 to 30 parts by mass, more preferably from 2 to 10 parts by mass, and even more preferably from 3 to 6 parts by mass, per 100 parts by mass of the total epoxy resin contained in the matrix resin.
[45] The prepreg according to any one of [1] to
[25] and
[34] to
[44] , wherein the matrix resin contains a liquid epoxy resin and a solid epoxy resin, and a mass ratio represented by [content of liquid epoxy resin] / [content of solid epoxy resin] is preferably 10 / 90 to 50 / 90, more preferably 20 / 80 to 40 / 60, and even more preferably 25 / 75 to 35 / 65.
[46] The prepreg according to any one of [1] to
[25] and
[34] to
[45] , wherein the matrix resin contains an epoxy resin and a (meth)acrylate monomer, and a mass ratio represented by [epoxy resin content] / [(meth)acrylate monomer content] is preferably 100 / 75 to 100 / 5, more preferably 100 / 50 to 100 / 10, and even more preferably 100 / 30 to 100 / 20.
[47] The prepreg described in any one of [1] to
[25] and
[34] to
[46] , wherein when a resin plate having a thickness of 2 mm is formed from the matrix resin, the bending strength of the resin plate is preferably 170 MPa or more and 200 MPa or less, and more preferably 175 MPa or more and 190 MPa or less.
[48] The prepreg according to any one of [1] to
[25] and
[34] to
[47] , wherein when a resin plate having a thickness of 2 mm is formed from the matrix resin, the resin plate has a flexural modulus of preferably 3.60 GPa or more and 10.0 GPa or less, and more preferably 3.65 GPa or more and 5.0 GPa or less.
[49] The prepreg according to any one of [1] to
[25] and
[34] to
[48] , wherein the maximum stress-strain of a resin plate having a thickness of 2 mm formed from the matrix resin is preferably greater than 0% and less than 7.0%, and more preferably greater than 0% and less than 6.5%.
[50] The prepreg according to any one of [1] to
[25] and
[34] to
[49] , wherein when a resin plate having a thickness of 2 mm is formed from the matrix resin, the breaking strain of the resin plate is preferably 8.0% or more and 20.0% or less, and more preferably 8.5% or more and 15% or less.
[51] The prepreg according to any one of the items [1] to
[25] and
[34] to
[50] , wherein the matrix resin contains a (meth)acrylate monomer, and the (meth)acrylate monomer is preferably a trifunctional (meth)acrylate monomer; more preferably a trifunctional (meth)acrylate monomer obtained by esterification through a reaction between tris(2-hydroxyethyl)isocyanurate and (meth)acrylic acid; and even more preferably a trifunctional (meth)acrylate monomer represented by the following formula (2):
[0011] [ka]
[0012]
[52] A method for producing a prepreg according to any one of the items [1] to
[25] and
[34] to
[51] , comprising an impregnation step in which a film made of the matrix resin is laminated and heated and pressurized to impregnate a reinforcing fiber base material containing the carbon fiber or reinforcing fiber with the matrix resin.
[0013] The present invention also has the following embodiments [1a] to [22a]. [1a] A resin composition containing an epoxy resin, a curing agent, a monofunctional (meth)acrylate monomer having a molecular weight of 200 or more, and a polyfunctional (meth)acrylate monomer. [2a] The resin composition according to [1a], wherein the curing agent comprises a component (b1) which is at least one selected from the group consisting of dicyandiamide, ureas, imidazoles, and aromatic amines. [3a] The resin composition according to [2a], wherein the curing agent contains dicyandiamide. [4a] The resin composition according to any one of [1a] to [3a], wherein the curing agent contains a peroxide-based compound. [5a] The resin composition according to any one of [1a] to [4a], wherein the content of the polyfunctional (meth)acrylate monomer in the resin composition is greater than the content of the monofunctional (meth)acrylate monomer having a molecular weight of 200 or more. [6a] The resin composition according to any one of [1a] to [5a], wherein the monofunctional (meth)acrylate monomer having a molecular weight of 200 or more includes at least one monomer selected from isobornyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, phenoxyethyl (meth)acrylate, dicyclopentenyl (meth)acrylate, and dicyclopentanyl (meth)acrylate. [7a] The resin composition according to any one of [1a] to [6a], wherein the polyfunctional (meth)acrylate monomer comprises an acrylate monomer represented by the following structural formula (1):
[0014] [ka]
[0015] (In formula (1), each X independently represents ethylene oxide or propylene oxide, each n, m, and l independently represents an integer of 0 to 10, and Y independently represents an acryloyl group or a hydrogen atom.) [8a] The resin composition according to any one of [1a] to [7a], comprising 5 to 45 parts by mass of the monofunctional (meth)acrylate monomer having a molecular weight of 200 or more and the polyfunctional (meth)acrylate monomer relative to 100 parts by mass of the total epoxy resin. [9a] The resin composition according to any one of [1a] to [8a], wherein a cured product obtained by curing the resin composition under the following curing conditions has a sea-island phase-separated structure composed of domains X and Y, the domains X constitute islands having a size R of 400 nm or less as measured by the following measurement method, and a ratio L / R of the distance L between the domains X to the size R is 1.1 or more. Curing conditions; The matrix resin is injected between two glass plates to form a plate of 2 mm thickness, and the oven atmosphere temperature is raised to 130°C at a rate of 2°C / min and maintained at 130°C for 90 minutes. Measurement conditions; As a pretreatment, a section of 60 to 90 nm thick is cut from the cross section of the cured material using an ultramicrotome, and the obtained section is exposed to RuO4 vapor for 7 minutes to perform electronic staining. Alternatively, a section of 60 to 90 nm thick is cut from the cross section of the cured material that has been previously exposed to OsO4 vapor for 16 hours using an ultramicrotome. The phase separation structure of the section that has been electronically stained by pretreatment is observed using a transmission electron microscope (TEM) with the acceleration voltage set to 80 kV, and a TEM image is obtained. The obtained TEM image is smoothed and background subtracted using image analysis software, and the boundary of the binarized image is detected. The size R is the median of the maximum Feret's diameter of the domain X. The distance L between domains X is the median of the distance from the center of gravity of domain X to the center of gravity of another domain X that is closest to the domain X. [10a] A resin composition comprising an epoxy resin, wherein when the resin composition is cured under the curing conditions described in [9a], a cured product has a sea-island phase-separated structure consisting of domains X and Y, which constitutes island parts having a size R of 400 nm or less as measured by the measurement method described in [9a], and the ratio L / R of the distance L between the domains X to the size R is 1.1 or more. [11a] The resin composition according to [10a], wherein the ratio L / R is 100 or less. [12a] The resin composition according to [10a] or [11a], wherein the size R is 1 nm or more. [13a] The resin composition according to any one of [10a] to [12a], wherein the matrix resin comprises the following components (A) and (B): Component (A): (Meth)acrylate monomer Component (B): Hardener. [14a] The resin composition according to [13a], wherein the component (A) contains a monofunctional (meth)acrylate monomer. [15a] The resin composition according to [13a] or [14a], wherein the component (A) contains a polyfunctional (meth)acrylate monomer. [16a] The resin composition according to any one of [10a] to [15a], wherein the domain X contains a polymer of a (meth)acrylate monomer. [17a] The resin composition according to any one of [10a] to [16a], wherein the domain Y contains a cured product of an epoxy resin. [18a] The resin composition according to any one of [13a] to [17a], wherein the component (B) includes a component (b1) which is at least one selected from the group consisting of dicyandiamide, ureas, imidazoles, and aromatic amines. [19a] The resin composition according to [18a], wherein the component (b1) is contained in an amount of 1 to 15 parts by mass per 100 parts by mass of the total epoxy resin contained in the matrix resin. [20a] The resin composition according to any one of [13a] to [19a], wherein the component (B) contains a peroxide-based compound. [21a] The resin composition according to any one of [10a] to [20a], wherein the component (A) is contained in an amount of 5 to 45 parts by mass relative to 100 parts by mass of the total epoxy resin. [22a] A film made of the resin composition according to any one of the items [1a] to [21a]. Effect of the Invention
[0016] According to the present invention, it is possible to provide a cured product and a fiber-reinforced plastic having excellent toughness and elastic modulus. [Brief description of the drawings]
[0017] [Figure 1] FIG. 1 is a cross-sectional view of a cured matrix resin. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] [Prepreg] One form of the prepreg includes carbon fibers and a matrix resin. The matrix resin includes an epoxy resin, and when the matrix resin is cured under the following curing conditions, the cured product has a sea-island phase-separated structure consisting of domains X and Y, and the domains X form islands having a size R of 400 nm or less as measured by the following measurement method, and the ratio L / R of the distance L between domains X to the size R is 1.1 or more. Although there is a trade-off between elastic modulus and toughness, the phase-separated structure allows a domain with excellent elastic modulus and a domain with excellent toughness to coexist, making it possible to achieve both elastic modulus and toughness. The matrix resin may include the following components (A) and / or (B). Component (A): (Meth)acrylate monomer Component (B): Hardener Curing conditions; The matrix resin is injected between two glass plates to form a plate of 2 mm thickness, and the oven atmosphere temperature is raised to 130°C at a rate of 2°C / min and maintained at 130°C for 90 minutes. For the curing of the matrix resin, it is preferable to use only the matrix resin taken out from the prepreg or the matrix resin before impregnation. In addition, a piece may be obtained from the matrix resin that has been cured by flowing so as to fill the cut-out portion after stacking the prepreg with a cut-out portion and curing the entire laminate under the above conditions. Alternatively, a piece may be obtained from the cured product of the matrix resin that has oozed out from the carbon fiber substrate when the prepreg is heated and cured under pressure. Measurement conditions; As a pretreatment, a section of 60-90 nm thick is cut from the cross section of the cured product using an ultramicrotome, and the obtained section is exposed to RuO4 vapor for 7 minutes to perform electronic staining. Alternatively, a section of 60-90 nm thick is cut from the cross section of the cured product that has been previously exposed to OsO4 vapor for 16 hours using an ultramicrotome to obtain an electronically stained section. The cross section of the cured product can be 500 μm x 300 μm in size. The phase separation structure of the electronically stained section is observed using a transmission electron microscope (TEM) with the acceleration voltage set to 80 kV, and a TEM image is obtained. The obtained TEM image is smoothed and background subtracted using image analysis software, and the boundary of the binarized image is detected. The size R is the median of the maximum Feret's diameter of the domain X. The distance L between the domains X is the median of the distance from the center of gravity of the domain X to the center of gravity of the nearest other domain X.
[0019] <Sea-island phase separation structure> A phase-separated structure can be formed when two or more phases are composed mainly of different components among the components that make up the cured product. The components may be in a homogeneous, compatible state before curing, and then separated into two or more phases during the curing process. A phase-separated structure in which the maximum Feret diameter of the phases composed mainly of different components is less than 1 nm is considered to be in a compatible state.
[0020] The phase separation structure can be observed by observing a smooth cross section of the cured product using a scanning electron microscope, a transmission electron microscope, an atomic force microscope, or the like. The smooth cross section of the cured product can be obtained by using a microtome method or a freeze fracturing method if the cured product does not contain reinforcing fibers, and can be obtained by using a mechanical polishing method, an ion milling method, a focused ion beam processing method, or the like if the cured product contains reinforcing fibers. The cross section to be observed is preferably smooth (mirror surface) to the extent that light is uniformly reflected. When using an electron microscope, electronic staining may be performed as necessary. Staining can be performed using a normal staining agent such as RuO4 or OsO4. If there are two or more domains with different contrasts in the electron microscope image, it can be determined that a phase separation structure of two or more phases exists.
[0021] A sea-island phase separation structure is formed when the cured product has a continuous phase and a dispersed phase. As shown in FIG. 1, in a cross section of a cured product obtained by curing a prepreg under specific conditions, the phase indicated by 2 corresponding to the islands is designated as domain X, and the phase indicated by 1 corresponding to the sea is designated as domain Y. The size R of domain X is 400 nm or less, and from the viewpoint of toughness, it is preferable that it is 300 nm or less. From the viewpoint of achieving both toughness and elastic modulus, the size R is preferably 1 nm or more, and more preferably 20 nm or more. The ratio L / R of the distance L between domains X to the size R is 1.1 or more, and since it is effective for improving toughness that the domains X are uniformly dispersed without agglomeration, it is preferable that it is 1.25 or more, and more preferably 1.5 or more. From the viewpoint of exhibiting toughness by maintaining the distance between domains X at a moderate level, it is preferable that it is 100 or less.
[0022] The size R of a domain X is defined as the median of the maximum distance (maximum Feret's diameter) between the parallel tangents to the opposing contour lines for each domain X, as shown in 3 of Figure 1. The distance L between domains X is defined as the median of the distance (nearest neighbor distance) from the center of gravity of a domain X to the center of gravity of the nearest other domain X. Each median is determined by analyzing 150 or more domains X and obtaining the distribution of their sizes R and distances L. If domains smaller than the domain to be analyzed, for example 1 / 20, are extracted, they can be removed as noise.
[0023] From the viewpoint of improving toughness, it is preferable that domain X contains a polymer of a (meth)acrylate monomer. From the viewpoint of adhesion to carbon fibers, it is preferable that domain Y, which is a continuous phase, contains a cured product of an epoxy resin that has excellent adhesion to carbon fibers.
[0024] The size R of the domain X can be increased by at least one of the following adjustment methods: (1a) A (meth)acrylate monomer is contained in the matrix resin, and its mixing ratio is increased. (2a) A (meth)acrylate monomer is contained in the matrix resin, and the ratio of polyfunctional monomers in the (meth)acrylate monomer is reduced. (3a) The matrix resin contains two or more types of epoxy resins with different molecular weights, and the proportion of low molecular weight components in the epoxy resin is increased.
[0025] The size R of the domain X can be reduced by at least one of the following adjustment methods: (1b) The matrix resin contains a (meth)acrylate monomer, and its mixing ratio is reduced. (2b) A (meth)acrylate monomer is contained in the matrix resin, and the proportion of polyfunctional monomers in the (meth)acrylate monomer is increased. (3b) The matrix resin contains two or more types of epoxy resins with different molecular weights, and the proportion of low molecular weight components in the epoxy resin is reduced.
[0026] <Component (A)> Component (A) is a (meth)acrylate monomer. Component (A) contributes to improving the strength, elastic modulus, and toughness of the cured product. Examples of the (meth)acrylate monomer include monofunctional (meth)acrylate monomers and difunctional or higher (meth)acrylate monomers (sometimes referred to as polyfunctional (meth)acrylate monomers). One of these may be used alone, or two or more may be used in combination. In order to balance the strength, elastic modulus, and toughness of the cured product, and from the viewpoint of dimensional stability during molding, it is preferable to use a monofunctional (meth)acrylate monomer and a di- to tetrafunctional (meth)acrylate monomer in combination. Since the impregnation temperature can be increased when used in a prepreg, the molecular weight of the (meth)acrylate monomer is preferably 200 or more, and more preferably 250 or more. From the viewpoint of uniform dispersion in the matrix resin, the molecular weight is preferably 2000 or less, and more preferably 1500 or less. As the polyfunctional (meth)acrylate monomer, a monomer having a structural formula represented by the following formula (1) is preferred from the viewpoint of toughness of the cured product.
[0027] [ka]
[0028] (In formula (1), each X independently represents ethylene oxide or propylene oxide, each n, m, and l independently represents an integer of 0 to 10, and Y independently represents an acryloyl group or a hydrogen atom.)
[0029] Examples of monofunctional (meth)acrylate monomers include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 4-hydroxybenzyl (meth)acrylate, 4-hydroxyphenyl (meth)acrylate, cyclohexanedimethanol mono(meth)acrylate, tetrahydrofurfuryl (meth)acrylate, phenoxyethyl (meth)acrylate, cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, norbornyl (meth)acrylate, 2-(meth)acryloyloxymethyl-2-methylbicycloheptane, adamantyl (meth)acrylate, benzyl (meth)acrylate, phenyl (meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentanyl (meth)acrylate, tetracyclododecanyl (meth)acrylate, methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, ) acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, icosyl (meth)acrylate, 2-methoxyethyl (meth)acrylate, 3-methoxybutyl (meth)acrylate, methoxytriethylene glycol (meth)acrylate, butoxyethyl (meth)acrylate, methoxydipropylene glycol (meth)acrylate, polyethylene glycol (meth)acrylate, polypropylene glycol (meth)acrylate, polyethylene glycol monomethyl ether (meth)acrylate, polypropylene glycol monomethyl (meth)acrylate, 4-acryloyloxymethyl-2-methyl-2-ethyl-1,3-dioxolane, 4-acryloyloxymethyl-2-methyl-2-isobutyl-1,Examples of (meth)acrylic acid esters include 3-dioxolane, o-phenylphenol (meth)acrylate, ethoxylated o-phenylphenol (meth)acrylate, N-(meth)acryloyloxyethylhexahydrophthalimide, paracumylphenol (meth)acrylate, ethoxylated paracumylphenol (meth)acrylate, and trimethylolpropane formal (meth)acrylate. From the viewpoints of improving the toughness of the cured product and suppressing the volatilization of the monomer at the impregnation temperature during the preparation of the prepreg, isobornyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, phenoxyethyl (meth)acrylate, dicyclopentenyl (meth)acrylate, and dicyclopentanyl (meth)acrylate are preferred.
[0030] Examples of bifunctional (meth)acrylate monomers include ethylene glycol, diethylene glycol, triethylene glycol, tetraethylene glycol, propylene glycol, dipropylene glycol, tripropylene glycol, tetrapropylene glycol, 1,3-butylene glycol, 1,4-butanediol, 1,5-pentanediol, neopentyl glycol, 3-methyl-1,5-pentanediol, 2,4-diethyl-1,5-pentanediol, 1,6-hexanediol, 1,9-nonanediol, 2- Examples of the diols include methyl-1,8-octanediol, 1,10-decanediol, neopentyl glycol hydroxypivalate, tricyclodecane dimethanol, cyclohexane dimethanol, bisphenol A, hydrogenated bisphenol A, dioxane glycol, and bisphenoxyfluorene ethanol, and di(meth)acrylates obtained by esterifying diols obtained by reacting these diols with (meth)acrylic acid. From the viewpoint of compatibility with epoxy resins, bifunctional (meth)acrylate monomers having a glycol skeleton are preferred, and from the viewpoint of obtaining high mechanical properties, bifunctional (meth)acrylate monomers having a bisphenol A skeleton are preferred.
[0031] Examples of trifunctional (meth)acrylate monomers include tri(meth)acrylates obtained by esterifying alcohols obtained by adding ethylene oxide, propylene oxide, caprolactone, or the like to triols or tetraols such as trimethylolpropane, tris(2-hydroxyethyl)isocyanurate, glycerol, and pentaerythritol with (meth)acrylic acid. Trifunctional (meth)acrylate monomers obtained from tris(2-hydroxyethyl)isocyanurate are preferred, trifunctional (meth)acrylate monomers obtained by esterifying tris(2-hydroxyethyl)isocyanurate with (meth)acrylic acid are more preferred, and trifunctional (meth)acrylate monomers represented by the following formula (2) are even more preferred.
[0032] [ka]
[0033] Examples of the tetrafunctional or higher (meth)acrylate compound include polyols such as ditrimethylolpropane, pentaerythritol, dipentaerythritol, and tripentaerythritol, as well as poly(meth)acrylates obtained by esterifying polyols obtained by reacting these polyols with (meth)acrylic acid.
[0034] The matrix resin may contain the following component (C) which is different from component (A). The content may be 0.5 parts by mass or more and 30 parts by mass or less based on 100 parts by mass of the total epoxy resin. Component (C): (meth)acrylate oligomer Examples of (meth)acrylate oligomers include urethane (meth)acrylates obtained by directly adding hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, pentaerythritol triacrylate, etc. to at least one of polyisocyanates such as 1,3- and 1,4-diisocyanatocyclohexane, 3-isocyanatomethyl-3,5,5-trimethylcyclohexyl isocyanate, 4,4'-methylenedicyclohexyl diisocyanate, 2,4-methylenedicyclohexyl diisocyanate, 2,2'-methylenedicyclohexyl diisocyanate, tolylenediisocyanate, diphenylmethane diisocyanate, and hexamethylene diisocyanate. These can be used alone or in combination of two or more. Other examples of the monomers that can be used include vinyl ester monomers such as vinyl acetate, vinyl butyrate, N-vinylformamide, N-vinylacetamide, N-vinyl-2-pyrrolidone, N-vinylcaprolactam, and divinyl adipate; vinyl ethers such as ethyl vinyl ether and phenyl vinyl ether; and acrylamides such as acrylamide, N,N-dimethylacrylamide, N,N-dimethylmethacrylamide, N-methylolacrylamide, N-methoxymethylacrylamide, N-butoxymethylacrylamide, Nt-butylacrylamide, N-benzyl(meth)acrylamide, N-phenyl(meth)acrylamide, N-(4-hydroxybenzyl)(meth)acrylamide, N-(4-hydroxyphenyl)(meth)acrylamide, acryloylmorpholine, hydroxyethylacrylamide, and methylenebisacrylamide.
[0035] The component (A) is preferably contained in an amount of 5 parts by mass or more, more preferably 10 parts by mass or more, based on 100 parts by mass of the total epoxy resin in the prepreg. The component (A) is preferably contained in an amount of 45 parts by mass or less, more preferably 40 parts by mass or less, based on 100 parts by mass of the total epoxy resin in the prepreg. When the content of the component (A) is within this range, the size of the phase separation structure is within an appropriate range, and the balance of strength, elastic modulus, and strain is good. The content ratio of the polyfunctional (meth)acrylate monomer in the component (A) is preferably 5% by mass or more, more preferably 30% by mass or more, and even more preferably 70% by mass or more, because a cured product having excellent interfacial adhesion with the epoxy component can be obtained and has excellent strength. From the viewpoint of controlling the phase separation structure and improving toughness associated therewith, the content is preferably 90% by mass or less, more preferably 80% by mass or less. The content of the monofunctional (meth)acrylate monomer in component (A) is preferably 1% by mass or more, more preferably 10% by mass or more, and even more preferably 20% by mass or more, from the viewpoint of controlling the phase separation structure and improving toughness accordingly. In order to suppress a decrease in the elastic modulus, the content is preferably 70% by mass or less, more preferably 30% by mass or less. The content ratio of the polyfunctional (meth)acrylate monomer and the monofunctional (meth)acrylate monomer can be determined by a separation analysis method such as gas chromatography or liquid chromatography in the case of a prepreg, and can be determined by pyrolysis gas chromatography in the case of a cured product.
[0036] <Ingredient (B)> Component (B) is a curing agent. It is preferable to include component (b1) that cures the epoxy resin or (b2) that cures component (A), and it is more preferable to use them in combination. As component (b1), dicyandiamide, ureas, imidazoles, aromatic amines, other amine-based curing agents, acid anhydrides, boron chloride amine complexes, etc. can be used, but it is particularly preferable to use at least one curing agent selected from dicyandiamide, ureas, imidazoles, and aromatic amines.
[0037] The content of component (b1) is preferably 1 part by mass or more, more preferably 2 parts by mass or more, per 100 parts by mass of the total epoxy resin contained in the matrix resin from the viewpoint of promoting the curing of the epoxy resin, and is preferably 15 parts by mass or less, more preferably 12 parts by mass or less, from the viewpoint of suppressing poor appearance after curing.
[0038] Dicyandiamide has a high melting point and is less compatible with epoxy resins in the low temperature range, so that when used as a curing agent (b1), the pot life of the resin composition or prepreg is excellent. Commercially available dicyandiamide products include, for example, DICY7, DICY15 (all manufactured by Mitsubishi Chemical Corporation), and DICYANEX1400F (manufactured by Evonik Japan Co., Ltd.). The content of dicyandiamide is preferably 1 to 15 parts by mass, more preferably 2 to 10 parts by mass, relative to 100 parts by mass of the total epoxy resin contained in the matrix resin. The mole number of active hydrogen of dicyandiamide is preferably 0.4 to 1 times the total mole number of epoxy groups of the epoxy resin contained in the matrix resin. From the viewpoint of heat resistance of the cured product, the mole number of active hydrogen of dicyandiamide is more preferably 0.5 to 0.8 times.
[0039] Ureas activate epoxy groups by heating. Examples of ureas include aromatic dimethylurea in which a dimethylureido group is bonded to an aromatic ring, and aliphatic dimethylurea in which a dimethylureido group is bonded to an aliphatic compound. Among these, aromatic dimethylurea is preferred because it has a high curing rate and tends to increase the heat resistance and bending strength of the cured product.
[0040] Examples of aromatic dimethylurea include phenyl dimethylurea, methylene bis(phenyl dimethylurea), and tolylene bis(dimethylurea). Specific examples include 4,4'-methylene bis(phenyl dimethylurea) (MBPDMU), 3-phenyl-1,1-dimethylurea (PDMU), 3-(3,4-dichlorophenyl)-1,1-dimethylurea (DCMU), 3-(3-chloro-4-methylphenyl)-1,1-dimethylurea, 2,4-bis(3,3-dimethylureido)toluene (TBDMU), and dimethylurea obtained from m-xylylene diisocyanate and dimethylamine. Among these, DCMU, MBPDMU, TBDMU, and PDMU are more preferable in terms of curing acceleration ability and imparting heat resistance to the cured product. Examples of the aliphatic dimethylurea include dimethylurea obtained from isophorone diisocyanate and dimethylamine, dimethylurea obtained from hexamethylene diisocyanate and dimethylamine, etc. These may be used alone or in combination of two or more.
[0041] Commercially available ureas include DCMU, DCMU-99 (manufactured by Hodogaya Chemical Co., Ltd.), MBPDMU, Technicure MDU-11 (manufactured by A&C Catalysts); Omicure 52 (manufactured by PTI Japan Co., Ltd.), and the like, PDMU, Omicure 94 (manufactured by PTI Japan Co., Ltd.), TBDMU, Omicure 24 (manufactured by PTI Japan Co., Ltd.), U-CAT 3512T (manufactured by San-Apro Ltd.), and the like, and aliphatic dimethylurea, U-CAT 3513N (manufactured by San-Apro Ltd.), and the like.
[0042] The content of the ureas is preferably 1 to 15 parts by mass, more preferably 2 to 10 parts by mass, based on 100 parts by mass of the total epoxy resin contained in the matrix resin. If the content of the ureas is 1 part by mass or more, the curing of the epoxy resin is accelerated, and the mechanical properties of the cured product tend to be improved. On the other hand, if the content of the ureas is 15 parts by mass or less, the toughness of the cured product tends to be maintained at a high level.
[0043] Imidazoles have a nitrogen atom having an unshared electron pair in their structure, and can activate the epoxy group. As the imidazoles, imidazole, imidazole adduct, clathrate imidazole, microencapsulated imidazole, imidazole compound coordinated with a stabilizer, etc. can also be used.
[0044] Specific examples of imidazole include 2-methylimidazole, 2-ethyl-4-methylimidazole, 2-undecylimidazole, 2-heptadecylimidazole, 1,2-dimethylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, 1-benzyl-2-phenylimidazole, 1-benzyl-2-methylimidazole, 1-cyanoethyl-2-methylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-phenylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazolium trimellitate, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-phenylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazolium trimellitate, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-phenylimidazolium trimellitate, 2,4-diaminoethylimidazole, 1-cyanoethyl-2- ... 2,4-Diamino-6-(2'-methylimidazolyl-(1'))-ethyl-s-triazine, 2,4-Diamino-6-(2'-undecylimidazolyl-(1'))-ethyl-s-triazine, 2,4-Diamino-6-(2'-ethyl-4-methylimidazolyl-(1'))-ethyl-s-triazine, 2,4-Diamino-6-(2'-methylimidazolyl-(1'))-ethyl-s-triazine, isocyanide Examples of imidazoles that have been modified include, but are not limited to, 1-cyanoethyl-2-phenyl-4,5-di(2-cyanoethoxy)methylimidazole, 2-phenyl-4,5-dihydroxymethylimidazole, and 2-phenyl-4-methyl-5-hydroxymethylimidazole. Imidazoles that have been modified by adduct treatment, inclusion treatment with foreign molecules, microencapsulation treatment, or coordination with stabilizers are imidazoles that have been modified to reduce activity and promote cure while exhibiting excellent pot life at low temperatures.
[0045] Commercially available imidazole products include 2E4MZ, 2P4MZ, 2PZ-CN, C11Z-CNS, C11Z-A, 2MZA-PW, 2MA-OK, 2P4MHZ-PW, and 2PHZ-PW (all manufactured by Shikoku Chemical Industry Co., Ltd.). Commercially available imidazole adduct products include PN-50, PN-50J, PN-40, PN-40J, PN-31, PN-23, and PN-H (all manufactured by Ajinomoto Fine-Techno Co., Ltd.), which have a structure in which an imidazole compound is ring-opened and added to the epoxy group of an epoxy resin. Commercially available clathrate imidazole products include TIC-188, KM-188, HIPA-2P4MHZ, NIPA-2P4MHZ, TEP-2E4MZ, HIPA-2E4MZ, and NIPA-2E4MZ (all manufactured by Nippon Soda Co., Ltd.). Commercially available products of microencapsulated imidazole include Novacure HX3721, HX3722, HX3742, and HX3748 (all manufactured by Asahi Kasei E-Materials Corporation); and LC-80 (all manufactured by A&C Catalysts). The imidazole compound coordinated with a stabilizer can be prepared by combining Cureduct P-0505 (bisphenol A diglycidyl ether / 2-ethyl-4-methylimidazole adduct) manufactured by Shikoku Kasei Kogyo Co., Ltd., which is an imidazole adduct, with L-07N (epoxy-phenol-boric acid ester blend) manufactured by Shikoku Kasei Kogyo Co., Ltd. The same effect can be obtained by using imidazole compounds such as the various imidazoles and imidazole adducts listed above instead of Cureduct P-0505.
[0046] The content of the imidazoles is preferably 1 to 15 parts by mass, more preferably 2 to 10 parts by mass, based on 100 parts by mass of the total epoxy resin contained in the matrix resin. If the content of the imidazoles is 1 part by mass or more, the curing of the epoxy resin tends to be more accelerated. On the other hand, if the content of the imidazoles is 15 parts by mass or less, a cured product with better mechanical properties tends to be obtained.
[0047] Examples of aromatic amines include 3,3'-diisopropyl-4,4'-diaminodiphenylmethane, 3,3'-di-t-butyl-4,4'-diaminodiphenylmethane, 3,3'-diethyl-5,5'-dimethyl-4,4'-diaminodiphenylmethane, 3,3'-diisopropyl-5,5'-dimethyl-4,4'-diaminodiphenylmethane, 3,3'-di-t-butyl-5,5'-dimethyl-4,4'-diaminodiphenylmethane, 3,3',5,5'-tetraethyl-4,4'-diaminodiphenylmethane, 3,3'-diisopropyl-5,5'-diethyl-4,4'-diaminodiphenylmethane, nylmethane, 3,3'-di-t-butyl-5,5'-diethyl-4,4'-diaminodiphenylmethane, 3,3',5,5'-tetraisopropyl-4,4'-diaminodiphenylmethane, 3,3'-di-t-butyl-5,5'-diisopropyl-4,4'-diaminodiphenylmethane, 3,3',5,5'-tetra-t-butyl-4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenylsulfone, 3,3'-diaminodiphenylsulfone, m-phenylenediamine, m-xylylenediamine, diethyltoluenediamine, etc. Among them, 4,4'-diaminodiphenylsulfone and 3,3'-diaminodiphenylsulfone are preferred, which are excellent in heat resistance and elastic modulus, and further provide a cured product with a small decrease in heat resistance due to linear expansion coefficient and moisture absorption. 4,4'-diaminodiphenyl sulfone is preferred because it can maintain the tack life of the prepreg for a long period of time. 3,3'-diaminodiphenyl sulfone is preferred because it can increase the elastic modulus and toughness of the cured product. 4,4'-diaminodiphenyl sulfone and 3,3'-diaminodiphenyl sulfone may be used in combination. These aromatic amines may be used alone or in combination.
[0048] The content of aromatic amines is preferably 1 to 15 parts by mass, more preferably 2 to 10 parts by mass, based on 100 parts by mass of all epoxy resins contained in the matrix resin. If the content of aromatic amines is 1 part by mass or more, the heat resistance and elastic modulus of the cured product tend to be excellent. On the other hand, if the content of aromatic amines is 15 parts by mass or less, the toughness of the cured product tends to be excellent. The active hydrogen equivalent number of the amino group is preferably 0.5 to 1.5 times, more preferably 0.6 to 1.4 times, the epoxy equivalent number of all epoxy resins contained in the matrix resin. By making the blending amount of these epoxy resin curing agents 0.5 to 1.5 times, the elastic modulus, toughness and heat resistance of the resin cured product tend to be in a good range.
[0049] Commercially available aromatic amines include 4,4'-diaminodiphenyl sulfone such as Seikacure S (active hydrogen equivalent 62 g / eq, manufactured by Wakayama Seika Kogyo Co., Ltd.) and Sumicure S (active hydrogen equivalent 62 g / eq, manufactured by Sumitomo Chemical Co., Ltd.), and commercially available 3,3'-diaminodiphenyl sulfone such as 3,3'-DAS (active hydrogen equivalent 62 g / eq, manufactured by Mitsui Chemicals Fine Co., Ltd.). Other aromatic amines include MDA-220 (active hydrogen equivalent 50 g / eq, manufactured by Mitsui Chemicals, Inc.), "jER Cure (registered trademark)" W (active hydrogen equivalent 45 g / eq, manufactured by Mitsubishi Chemical Corporation), Lonzacure (registered trademark) M-DEA (active hydrogen equivalent 78 g / eq), "Lonzacure (registered trademark)" M-DIPA (active hydrogen equivalent 92 g / eq), "Lonzacure (registered trademark)" M-MIPA (active hydrogen equivalent 78 g / eq), and "Lonzacure (registered trademark)" DETDA 80 (active hydrogen equivalent 45 g / eq) (all manufactured by Lonza Corporation).
[0050] Other amine-based curing agents that can be used as component (b1) include metaphenylenediamine, diaminodiphenylmethane, metaxylenediamine, isophoronediamine, triethylenetetramine, etc. Acid anhydrides that can be used as component (b1) include hydrogenated methylnadic anhydride, methylhexahydrophthalic anhydride, etc.
[0051] An example of component (b2) is a radical polymerization initiator. As the radical polymerization initiator, a thermal radical polymerization initiator or a photoradical polymerization initiator can be used. Among them, it is more preferable to use a thermal radical polymerization initiator since radical polymerization can be initiated simultaneously with the thermal curing of the epoxy resin. As the thermal radical polymerization initiator, azo compounds and peroxide compounds can be used. Among them, peroxide compounds are preferable since they do not generate gas during thermal decomposition.
[0052] Examples of azo compounds include 2,2-azobis(isobutyronitrile), 2,2-azobis(2,4-dimethylvaleronitrile), dimethyl 2,2-azobis(2-methylpropionate), 2,2-azobis(2-methylbutyronitrile), 1,1-azobis(cyclohexane-1-carbonitrile), 2,2-azobis(N-butyl-2-methylpropionamide), and dimethyl 1,1-azobis(1-cyclohexanecarboxylate).
[0053] Examples of peroxide compounds include ketone peroxides such as methyl ethyl ketone peroxide (110°C) and acetylacetone peroxide (130°C), 1,1-di(t-butylperoxy)3,3,5-trimethylcyclohexane (95°C), 1,1-di(t-hexylperoxy)cyclohexane (87.1°C), 1,1-di(t-butylperoxy)cyclohexane (90.7°C), 2,2-di(t-butylperoxy)butane (103.1°C), and n-butyl 4,4-di(t-butylperoxy)valerate (104°C). .5°C), 2,2-di(4,4-di-t-butylperoxycyclohexyl)propane (94.7°C), 1,1-di(t-hexylperoxy)3,3,5-trimethylcyclohexane (86.7°C), 1,1-di(t-butylperoxy)cyclododecane (95°C), peroxyketals such as p-menthane hydroperoxide (128°C), diisopropylbenzene hydroperoxide (145.1°C), 1,1,3,3-tetramethylbutyl hydroperoxide (152.9°C), and cumene hydroperoxide (157. Hydroperoxides such as di(2-t-butylperoxyisopropyl)benzene (119.2°C), dicumyl peroxide (116.4°C), 2,5-dimethyl-2,5-di(t-butylperoxy)hexane (117.9°C), t-butylcumyl peroxide (119.5°C), di-t-hexyl peroxide (116.4°C), di-t-butyl peroxide (123.7°C), 2,5-dimethyl-2,5-di(t-butylperoxy)hexyne-3 (128. Dialkyl peroxides such as diisobutyryl peroxide (32.7°C), di(3,5,5-trimethylhexanoyl) peroxide (59.4°C), lauroyl peroxide (61.6°C), disuccinic acid peroxide (65.9°C), m-toluoyl peroxide (73.1°C), dibenzoyl peroxide (73.6°C), dioctanoyl peroxide (63°C), diacyl peroxides such as di-n-propyl peroxydicarbonate (40.3°C), diisopropyl peroxydicarbonate (40.5°C), di(4-t-butylcyclohexyl) peroxydicarbonate (40.8°C), di(2-ethylhexyl) peroxydicarbonate (43.6°C), di-sec-butyl peroxydicarbonate (40.5°C), di(3-methoxybutyl) peroxydicarbonate (43°C), and other peroxydicarbonates; cumyl peroxyneodecanoate (36.5°C), 1,1,3,3-tetramethylbutyl peroxyneodecanoate (37.5°C), and 1,1,3,3-tetramethylbutyl peroxyneodecanoate (38.5°C), and other peroxydicarbonates; ester (40.7°C), t-hexyl peroxy neodecanoate (44.5°C), t-butyl peroxy neodecanoate (46.4°C), t-hexyl peroxy pivalate (53.2°C), t-butyl peroxy pivalate (54.6°C), 1,1,3,3-tetramethylbutyl peroxy-2-ethylhexanoate (65.3°C), 2,5-dimethyl-2,5-di(2-ethylhexanoylperoxy)hexane (66.2°C), t- Hexylperoxy-2-ethylhexanoate (69.9°C), t-butylperoxy-2-ethylhexanoate (72.1°C), t-hexylperoxyisopropyl monocarbonate (95°C), t-butylperoxy-3,5,5-trimethylhexanoate (97.1°C), t-butylperoxylaurate (98.3°C), t-butylperoxyisopropyl monocarbonate (98.7°C), t-butylperoxy-2-ethyl Examples of peroxyesters include tert-hexyl monocarbonate (99°C), t-hexyl peroxybenzoate (99.4°C), 2,5-dimethyl-2,5-di(benzoylperoxy)hexane (99.7°C), t-butyl peroxyacetate (101.9°C), t-butyl peroxybenzoate (104.3°C), t-butyl peroxymaleic acid (96.1°C), and t-butyl peroxyisobutyrate (75°C). The values in parentheses indicate the 10-hour half-life temperature.
[0054] Examples of the photoradical polymerization initiator include benzophenone, 4,4-bis(diethylamino)benzophenone, 2,4,6-trimethylbenzophenone, methyl orthobenzoylbenzoate, 4-phenylbenzophenone, 2-hydroxy-1-[4-[4-(2-hydroxy-2-methyl-propionyl)benzyl]phenyl]-2-methylpropan-1-one, t-butylanthraquinone, 2-ethylanthraquinone, diethoxyacetophenone, 2-hydroxy-2-methyl-1-phenylpropan-1-one, benzyl dimethyl ketal, 1-hydroxycyclohexyl-phenyl ketone, and benzoin methyl ether. , benzoin ethyl ether, benzoin isopropyl ether, benzoin isobutyl ether, 2-methyl-[4-(methylthio)phenyl]-2-morpholino-1-propanone, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butanone-1, diethylthioxanthone, isopropylthioxanthone, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, bis(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide, bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, and methylbenzoyl formate.
[0055] In order to polymerize component (A) to obtain a high molecular weight, component (b2) preferably contains at least one peroxide-based compound selected from the group consisting of diacyl peroxides, alkyl peroxy esters, peroxydicarbonates, peroxyketals, dialkyl peroxides, and hydroperoxides.
[0056] The exemplified compounds can be used as component (b2) either alone or in combination of two or more. In terms of storage stability of the prepreg, compounds having a 10-hour half-life temperature of 70°C or higher are preferred, and compounds having a 10-hour half-life temperature of 100°C or higher are more preferred. In order to facilitate the polymerization of component (A) during the epoxy resin curing process, the 10-hour half-life temperature can be set to 150°C or lower.
[0057] From the viewpoint of promoting curing, the content of component (b2) is preferably 0.1 parts by mass or more, and more preferably 0.2 parts by mass or more, per 100 parts by mass of the total matrix resin, and from the viewpoint of storage stability of the prepreg, the content is preferably 5 parts by mass or less, and more preferably 3 parts by mass or less, per 100 parts by mass of the total matrix resin.
[0058] <Epoxy resin> Examples of epoxy resins include bisphenol A type epoxy resins, bisphenol F type epoxy resins, epoxy resins having an oxazolidone ring skeleton, novolac type epoxy resins, glycidylamine type epoxy resins, hydrophthalic acid type epoxy resins, bisphenol S type epoxy resins, resorcin type epoxy resins, hydroquinone type epoxy resins, bisphenoxyethanol fluorene type epoxy resins, bisphenol fluorene type epoxy resins, and biscresol fluorene type epoxy resins. Among these, one or more epoxy resins selected from bisphenol A type epoxy resins, bisphenol F type epoxy resins, epoxy resins having an oxazolidone ring skeleton, novolac type epoxy resins, and glycidylamine type epoxy resins are preferred. Liquid and solid epoxy resins, which will be described later, can be used in combination. By combining multiple types of epoxy resins, it is possible to obtain a prepreg having excellent handling properties and a fiber-reinforced plastic having excellent mechanical properties and heat resistance.
[0059] The liquid epoxy resin is an epoxy resin that is liquid at 25°C. The liquid epoxy resin contributes to improving the solubility of the thermoplastic resin and improving the strength, elastic modulus, and heat resistance of the cured product. The viscosity of the epoxy resin that is liquid at 25°C is preferably 500 Pa·s or less at 25°C, more preferably 300 Pa·s or less. Also, it is preferably 0.1 Pa·s or more. When the viscosity is in this range, the workability of the epoxy resin composition can be improved. The viscosity can be measured by applying periodic deformation (strain) to the sample with a rotational rheometer and detecting the resulting stress and phase difference. It is preferably a bisphenol type epoxy resin. The epoxy resin is preferably 70 parts by mass or more, more preferably 80 parts by mass or more, relative to 100 parts by mass of the matrix resin. It can be 95 parts by mass or less relative to 100 parts by mass of the matrix resin.
[0060] The content of the liquid epoxy resin is preferably 20 parts by mass or more and 80 parts by mass or less relative to 100 parts by mass of the total epoxy resin contained in the epoxy resin composition. Since a resin cured product excellent in strength and elastic modulus can be obtained, the lower limit of the content of the liquid epoxy resin is more preferably 25 parts by mass or more, and even more preferably 28 parts by mass or more. Since a cured product excellent in toughness can be obtained, the upper limit of the content of the liquid epoxy resin is more preferably 75 parts by mass or less, even more preferably 70 parts by mass or less, and particularly preferably 50 parts by mass or less. The content can be the amount mixed when preparing the resin composition.
[0061] Commercially available liquid epoxy resins include bisphenol A type epoxy resins (liquid epoxy resins) that are liquid at 25°C, such as jER827 (epoxy equivalent: 185 g / eq), jER828 (epoxy equivalent: 189 g / eq) (both manufactured by Mitsubishi Chemical Corporation), YD-127 (epoxy equivalent: 185 g / eq), YD-128 (epoxy equivalent: 189 g / eq) (both manufactured by Nippon Steel Chemical & Material Co., Ltd.), EPICLON840 (epoxy equivalent: 185 g / eq), EPICLON850 (epoxy equivalent: 189 g / eq) (both manufactured by DIC Corporation), DER331 (epoxy equivalent: 187 / eq), DER332 (epoxy equivalent: 173 g / eq) (The Dow Chemical Examples of bisphenol F type epoxy resins (liquid epoxy resins) that are liquid at 25°C include, but are not limited to, jER806 (epoxy equivalent 165g / eq), jER807 (epoxy equivalent 170g / eq) (all manufactured by Mitsubishi Chemical Corporation), YDF-170 (epoxy equivalent 170g / eq) (manufactured by Nippon Steel Chemical & Material Co., Ltd.), EPICLON830 (epoxy equivalent 170g / eq), EPICLON835 (epoxy equivalent 172g / eq) (all manufactured by DIC Corporation), and DER354 (epoxy equivalent 170g / eq) (all manufactured by The Dow Chemical Company). One of these may be used alone, or two or more may be used in combination.
[0062] By including a solid epoxy resin, the viscosity at room temperature can be increased, making the prepreg easier to handle. The solid epoxy resin is preferably an epoxy resin having a softening point of 70°C or higher. Bisphenol-type epoxy resins having a softening point of 70°C or higher, epoxy resins having an oxazolidone ring skeleton, and epoxy resins that have been pre-reacted with a curing agent can be used. The softening point is preferably 72°C or higher, more preferably 75°C or higher, since the resin cured product has excellent toughness. On the other hand, the softening point is preferably 150°C or lower, more preferably 145°C or lower, since the heat resistance of the resin cured product is appropriately maintained and a prepreg with excellent drapeability (mold shape conformability) can be obtained.
[0063] The content of the solid epoxy resin is preferably 10 parts by mass or more and 80 parts by mass or less with respect to 100 parts by mass of the total epoxy resin contained in the epoxy resin composition. The lower limit of the content of the solid epoxy resin is more preferably 13 parts by mass or more, and even more preferably 15 parts by mass or more, since a prepreg having excellent tackiness and a resin cured product having excellent toughness can be obtained. The upper limit of the content of the solid epoxy resin is more preferably 70 parts by mass or less, and even more preferably 60 parts by mass or less, since a prepreg having excellent mold shape conformability can be obtained. The content can be the amount mixed when preparing the resin composition.
[0064] Commercially available solid epoxy resins include bisphenol A type epoxy resins such as jER1055, jER1004, jER1007, and jER1009 (all trade names, manufactured by Mitsubishi Chemical Corporation), EPICLON2050, EPICLON3050, EPICLON4050, EPICLON7050, EPICLON HM-091, and EPICLON HM-101 (all trade names, manufactured by DIC Corporation), YD-902, YD-903N, YD-904, YD-907, YD-7910, YD-6020 (all trade names, manufactured by Nippon Steel Chemical & Material Co., Ltd.), etc., as bisphenol F type epoxy resins, jER4004P, jER4005P, jER4007P, jER4010P (all trade names, manufactured by Mitsubishi Chemical Corporation), YDF-2004, YDF-2005RD (all trade names, manufactured by Nippon Steel Chemical & Material Co., Ltd.), etc., as epoxy resins having an oxazolidone ring skeleton, AER4152, AER4151, LSA3301, LSA2102 (all trade names, manufactured by Asahi Kasei E-materials Corporation), ACR1348 (trade name, manufactured by ADEKA Corporation), DER852, DER858 (trade name, manufactured by THE DOW Examples of the epoxy resins include TSR-400 (trade name, manufactured by DIC Corporation), and YD-952 (trade name, manufactured by Nippon Steel Chemical & Material Co., Ltd.) As the solid epoxy resin, one of these may be used alone, or two or more of them may be used in combination.
[0065] The matrix resin may contain an epoxy resin other than the above-mentioned epoxy resin. Examples of other epoxy resins include bisphenol A type epoxy resins such as jER834 (trade name, manufactured by Mitsubishi Chemical Corporation), EPICLON860 (trade name, manufactured by DIC Corporation), and YD-134 (trade name, manufactured by Nippon Steel Chemical & Material Co., Ltd.), and novolac type epoxy resins such as EPICLON N-740 (trade name, manufactured by DIC Corporation) and YDPN-638 (trade name, manufactured by Nippon Steel Chemical & Material Co., Ltd.). One of these may be used alone, or two or more may be used in combination.
[0066] <Thermoplastic resins, additives> Thermoplastic resins can be used for the matrix resin composition. Examples of thermoplastic resins include polyamide, polyester, polycarbonate, polyethersulfone, polyphenylene ether, polyphenylene sulfide, polyetheretherketone, polyetherketone, polyimide, polytetrafluoroethylene, polyether, polyolefin, liquid crystal polymer, polyarylate, polysulfone, polyacrylonitrilestyrene, polystyrene, polyacrylonitrile, polymethyl methacrylate, ABS (acrylonitrile-butadiene-styrene copolymer), AES (acrylonitrile-ethylene propylene rubber-styrene copolymer), ASA (acrylonitrile-acrylic rubber-styrene copolymer), polyvinyl chloride, polyvinyl formal resin, phenoxy resin, block polymer, etc., but are not limited thereto. Among these, polyethersulfone, polyvinyl formal resin, and phenoxy resin are more preferable because they have excellent resin flow controllability to the reinforcing fibers. Polyvinyl formal resin is even more preferable because it has excellent resin flow controllability even when the amount of the resin is small. The thermoplastic resin may be used alone or in combination of two or more kinds.
[0067] The content of the thermoplastic resin is preferably 1 part by mass or more and 30 parts by mass or less, more preferably 2 parts by mass or more and 10 parts by mass or less, and even more preferably 3 parts by mass or more and 6 parts by mass or less, relative to 100 parts by mass of the total epoxy resin contained in the matrix resin. If the content of the thermoplastic resin is 1 part by mass or more, it is preferable because the resin flow control tends to be well exhibited. On the other hand, if the content of the thermoplastic resin is 30 parts by mass or less, it is preferable because the viscosity increase during resin impregnation is small.
[0068] Among the thermoplastic resins, phenoxy resin, polyethersulfone, polyetherimide, polyvinyl formal, and block polymers are preferred from the viewpoint of excellent resin flow controllability, etc. In particular, when phenoxy resin, polyethersulfone, and polyetherimide are used, the heat resistance and flame retardancy of the cured resin are further improved.
[0069] Examples of the additives include a curing accelerator for the epoxy resin, an inorganic filler, an internal mold release agent, an organic pigment, an inorganic pigment, etc. The epoxy resin composition may contain various known additives as necessary within a range that does not impair the effects of the present invention. Examples of additives include phosphorus-based flame retardants (phosphorus-containing epoxy resins, red phosphorus, phosphazene compounds, phosphates, phosphoric acid esters, etc.), inorganic flame retardants such as hydrated metal compounds (aluminum hydroxide, magnesium hydroxide, etc.), inorganic oxides and other auxiliary agents (antimony compounds, zinc borate, zinc stannate, Mo compounds, ZrO, zinc sulfide, zeolite, titanium oxide nanofiller, etc.), silicone oils, wetting and dispersing agents, antifoaming agents, defoaming agents, natural waxes, synthetic waxes, metal salts of linear fatty acids, acid amides, esters, paraffins, and other mold release agents, crystalline silica, fused silica, calcium silicate, alumina, calcium carbonate, talc, barium sulfate, and other powders, glass fibers, and inorganic fillers such as carbon fibers, colorants such as carbon black and red iron oxide, and silane coupling agents. These may be used alone or in combination of two or more.
[0070] <Method of manufacturing matrix resin composition> The matrix resin composition can be obtained, for example, by mixing the above-mentioned components. The matrix resin composition is preferably a thermosetting resin composition. Examples of a method for mixing the components include a method using a mixer such as a three-roll mill, a planetary mixer, a kneader, a homogenizer, or a homodisper. The matrix resin composition can be used, for example, for impregnating a reinforcing fiber substrate as described below in the manufacture of a prepreg. In addition, a film of the matrix resin composition can be obtained by applying the matrix resin composition to a release paper or the like and curing it. The viscosity of the matrix resin composition at 30°C can be 100 to 1,000,000 Pa·s.
[0071] <Reinforced fiber> The reinforcing fibers can be present in the prepreg as a reinforcing fiber substrate (aggregate of reinforcing fibers), and are preferably in the form of a sheet. The reinforcing fibers may be arranged in a single direction or in a random direction. Examples of the form of the reinforcing fiber substrate include a woven fabric of reinforcing fibers, a nonwoven fabric of reinforcing fibers, and a sheet in which long reinforcing fibers are aligned in one direction. The reinforcing fibers are preferably in the form of a sheet made of a bundle of reinforcing fibers in which continuous fibers are aligned in a single direction, in order to be able to mold a fiber-reinforced composite material having a high specific strength and specific modulus of elasticity, and are preferably in the form of a woven fabric of reinforcing fibers in order to be easy to handle.
[0072] Examples of the material of the reinforcing fiber include glass fiber, carbon fiber, aramid fiber, boron fiber, etc. From the viewpoint of the mechanical properties and weight reduction of the obtained fiber-reinforced plastic, the reinforcing fiber is preferably carbon fiber.
[0073] The fiber diameter of the carbon fiber is preferably 3 to 12 μm. The number of carbon fibers in the carbon fiber bundle is preferably 1,000 to 70,000. From the viewpoint of the rigidity of the obtained fiber reinforced composite material, the strand tensile strength of the carbon fiber is preferably 1.5 to 9 GPa, and the strand tensile modulus of the carbon fiber is preferably 150 to 260 GPa. Here, the strand tensile strength and strand tensile modulus of the carbon fiber are values measured in accordance with JIS R7601:1986.
[0074] <Prepreg manufacturing method> The prepreg is obtained, for example, by impregnating a reinforcing fiber substrate with a matrix resin composition. Examples of a method for impregnating a reinforcing fiber substrate with a matrix resin composition include, but are not limited to, a wet method in which an epoxy resin composition is dissolved in a solvent such as methyl ethyl ketone or methanol to reduce the viscosity and then impregnated into a reinforcing fiber substrate; and a hot melt method (dry method) in which a matrix resin composition is heated to reduce the viscosity and then impregnated into a reinforcing fiber substrate. The impregnation temperature is set according to the viscosity of the matrix resin, but is preferably 40 to 90°C, more preferably 50 to 80°C, from the viewpoint that the matrix resin does not start curing reaction and the matrix resin needs to be sufficiently impregnated into the reinforcing fiber.
[0075] The wet method is a method in which a reinforcing fiber substrate is immersed in a solution of a matrix resin composition, then pulled up, and the solvent is evaporated using an oven or the like. The hot melt method includes a method in which a matrix resin composition whose viscosity has been reduced by heating is directly impregnated into a reinforcing fiber substrate, and a method in which the matrix resin composition is once applied to the surface of a substrate such as release paper to prepare a film, and then the film is layered on both sides or one side of the reinforcing fiber substrate, and the reinforcing fiber substrate is impregnated with the resin by heating and pressurizing. The coating layer obtained by applying the coating to the surface of a substrate such as release paper may be used in the hot melt method as it is, or may be used in the hot melt method after the coating layer is cured. The hot melt method is preferable because there is substantially no solvent remaining in the prepreg.
[0076] The content of the matrix resin composition in the prepreg (hereinafter referred to as "resin content") is preferably 15 to 50 mass %, more preferably 20 to 45 mass %, and even more preferably 25 to 40 mass %, based on the total mass of the prepreg. If the resin content is equal to or more than the lower limit, the adhesion between the reinforcing fibers and the matrix resin can be sufficiently ensured, and if it is equal to or less than the upper limit, the mechanical properties of the fiber reinforced plastic are further improved.
[0077] [Fiber reinforced plastics] Fiber-reinforced plastics are obtained by curing prepregs. That is, fiber-reinforced plastics include a cured product of a matrix resin composition contained in the prepregs and reinforcing fibers. The cured product can be a laminate in which two or more prepregs are laminated. For example, after laminating two or more of the above-mentioned prepregs, the laminate obtained is molded by applying pressure to the laminate and then heating and curing the laminate, thereby obtaining a molded product made of fiber-reinforced plastics. A prepreg made of a thermoplastic resin composition and reinforcing fibers other than the prepregs described above, or a prepreg made of an epoxy resin composition and reinforcing fibers may be laminated.
[0078] Examples of the molding method include, but are not limited to, press molding, autoclave molding, bagging molding, wrapping tape, internal pressure molding, sheet wrap molding, RTM (Resin Transfer Molding), VaRTM (Vacuum assisted Resin Transfer Molding), filament winding, RFI (Resin Film Infusion), etc., which are methods for impregnating a matrix resin composition into a reinforced fiber filament or preform and curing it to obtain a molded product. Press molding is preferred from the viewpoint of high productivity and easy production of high-quality fiber reinforced plastic.
[0079] When fiber-reinforced plastics are produced by press molding, it is preferable to clamp the prepreg or a preform produced by laminating the prepregs in a mold previously adjusted to the curing temperature, and apply heat and pressure to cure the prepreg or preform. The temperature inside the mold during press molding is preferably 100 to 160° C. In addition, it is preferable to cure the prepreg or preform for 1 to 20 minutes under conditions of 1 to 15 MPa. EXAMPLES
[0080] The present invention will be described in more detail below with reference to examples, but the present invention is not limited thereto. The raw materials used in the examples and comparative examples are shown below.
[0081] "Raw material" <Epoxy resin> jER807: Liquid bisphenol F type epoxy resin (manufactured by Mitsubishi Chemical Corporation, product name "jER 807"). jER828: Liquid bisphenol A type epoxy resin (manufactured by Mitsubishi Chemical Corporation, product name "jER 828"). jER4007P: Solid bisphenol F type epoxy resin (manufactured by Mitsubishi Chemical Corporation, product name "jER 4007P"). jER1004: Solid bisphenol A type epoxy resin (manufactured by Mitsubishi Chemical Corporation, product name "jER 1004"). YD-952: A solid epoxy resin having an oxazolidone ring structure (manufactured by Nippon Steel & Sumitomo Metal Corporation, product name "Epotohto YD-952"). MY0600: Triglycidyl-m-aminophenol (manufactured by Huntsman Japan, product name "ARALDITE MY 0600"). <Component (A)> A-9300S: Tris-(2-acryloxyethyl)isocyanurate (trifunctional, manufactured by Shin-Nakamura Chemical Co., Ltd., product name "NK Ester A-9300S"). IBXA: Isobornyl acrylate (monofunctional, manufactured by Osaka Organic Chemical Industry Ltd., product name "IBXA"). M-315: Isocyanuric acid EO-modified di- and triacrylate (trifunctional, manufactured by Toagosei Co., Ltd., product name "Aronix M-315"). FA-310AH: Phenoxyethyl acrylate (monofunctional, manufactured by Hitachi Chemical Co., Ltd., product name "FANCRYL FA-310AH" <Component (b1)> DICYANEX 1400F: Dicyandiamide (active hydrogen equivalent 21g / eq, manufactured by Evonik Japan Co., Ltd., product name "DICYANEX 1400F"). DCMU-99: 3-(3,4-dichlorophenyl)-1,1-dimethylurea (manufactured by Hodogaya Chemical Co., Ltd., product name "DCMU-99"). <Component (b2)> Percumyl D: Dicumyl peroxide (10-hour half-life temperature 116.4°C, manufactured by NOF Corporation, product name "Percumyl D"). <Thermoplastic resin> Vinylec E: Polyvinyl formal resin (manufactured by JNC Corporation, product name "Vinylec E"). Vinylec K: Polyvinyl formal resin (manufactured by JNC Corporation, product name "Vinylec K").
[0082] (Experimental Examples 1 to 4, Comparative Example 1) Resin compositions were prepared as follows using jER807, jER4007P, and YD-952 as epoxy resins, A-9300S and IBXA as component (A), DICYANEX 1400F and DCMU-99 as component (b1), Percumyl D as component (b2), and Vinylec E as a thermoplastic resin. First, according to the composition shown in Table 1, component (b1) (solid) and the liquid component of the epoxy resin were weighed into a container and mixed with stirring so that the mass ratio of the solid component to the liquid component was 1:1. This was further mixed finely in a triple roll mill to obtain a master batch containing a curing agent. Next, the epoxy resins and thermoplastic resins other than those used in the master batch containing the curing agent in the compositions shown in Table 1 were weighed into a flask, and the mixture was heated and stirred at 150°C using an oil bath to dissolve and mix. After that, when the mixture was cooled to about 65°C, the master batch containing the curing agent, component (A), and component (b2) were added and stirred to obtain an uncured thermosetting resin composition. Comparative Example 2 As shown in the formulation in Table 1, except that YD-952 was not used as the epoxy resin and no thermoplastic resin was used, and M-315 was used as component (A), thermosetting resin compositions were prepared in the same manner as in Experimental Examples 1 to 4 and Comparative Example 1, resin plates were produced, and the phase separation structure was measured, but no phase separation structure was confirmed. (Experimental Example 5, Comparative Example 3) Using jER828, jER1004, and MY0600 as epoxy resins, DICYANEX 1400F and DCMU-99 as component (b1), and Vinylec K as a thermoplastic resin, resin compositions were prepared as follows. First, according to the composition shown in Table 1, component (b1) (solid) and the liquid component of the epoxy resin were weighed into a container and mixed with stirring so that the mass ratio of the solid component to the liquid component was 1:1. This was further mixed finely in a triple roll mill to obtain a master batch containing a curing agent. Next, the epoxy resins and thermoplastic resins other than those used in the master batch containing the curing agent in the compositions shown in Table 1 were weighed into a flask, and were dissolved and mixed by heating and stirring at 150°C using an oil bath. After that, when the mixture was cooled to about 65°C, the master batch containing the curing agent was added and stirred and mixed to obtain an uncured thermosetting resin composition.
[0083] "Making resin plates" The uncured thermosetting resin composition was poured between two glass plates and formed into a plate. The temperature was increased at a rate of 2°C / min, and the composition was heated and cured by holding the composition at an oven ambient temperature of 130°C for 90 minutes to produce a resin plate 2 mm thick.
[0084] The prepared resin plate was subjected to various measurements and evaluations according to the following evaluation methods. The results are shown in Table 1.
[0085] "Measurement of bending strength, bending modulus, maximum stress strain, and breaking strain of resin plate" The resin plate with a thickness of 2 mm obtained in the above "Preparation of resin plate" was processed to a length of 60 mm x width of 8 mm to obtain a test piece. The test piece was measured for bending strength, bending modulus, maximum stress strain, and breaking strain of the resin plate under conditions of a crosshead speed of 2 mm / min using a universal testing machine (manufactured by INSTRON, "INSTRON 5965") equipped with a three-point bending jig (indenter R = 3.2 mm, support R = 3.2 mm, distance between supports (L) = 32 mm) under an environment of 23°C temperature and 50% RH. Specifically, the bending modulus (unit: GPa) was calculated by the secant method in the bending strain range of 0.05 to 0.25% using the stress-strain curve obtained under the above measurement conditions. In addition, the maximum bending stress of the stress-strain curve obtained under the above measurement conditions was obtained as bending strength (unit: MPa), and the bending strain at the maximum bending stress was obtained as maximum stress strain (unit: %). The bending strain at which the test piece broke under the above measurement conditions was obtained as the breaking strain (unit: %).
[0086] "Measurement of phase separation structure" From the 2 mm-thick resin plate obtained in the above "Preparation of resin plate", ultrathin sections with a thickness of 70 nm were cut out, and the obtained sections were subjected to electron staining by exposing them to RuO4 vapor for 7 minutes. The phase separation structure of the stained ultrathin sections was observed using a transmission electron microscope (TEM) with an acceleration voltage set to 80 kV. The domain X size R and the inter-domain X distance L were measured by analyzing the obtained TEM images using the image analysis software ImageJ. The median of the maximum Feret diameter of the domain X was taken as the domain X size R, and the median of the nearest neighbor distance of the domain X was taken as the inter-domain X distance L. The domain X size R is the median of the maximum distance (maximum Feret diameter) between the parallel tangents that are in contact with the opposing contour lines for each domain X. In addition, the inter-domain X distance L is the median of the distance (nearest neighbor distance) from the center of gravity of a certain domain X to the center of gravity of the nearest neighbor domain X. Each median was obtained from the distribution of the size R and distance L of 150 or more domains X analyzed. TEM equipment: JEM-1400Flash (manufactured by JEOL Ltd.) Conditions: Accelerating voltage 80 kV Observation magnification: 3000x
[0087] [Table 1]
[0088] (In Table 1, the content of each component is indicated by parts by mass.)
[0089] The resin compositions prepared in Experimental Examples 1 to 4 exhibited superior results in modulus of elasticity and breaking strain than Comparative Example 1. No phase separation structure was observed in Comparative Example 2. The resin composition prepared in Experimental Example 5 exhibited superior results in breaking strain than Comparative Example 3. It is believed that the fiber reinforced plastic obtained by using the resin compositions prepared in the Experimental Examples in a prepreg and curing the prepreg has excellent modulus of elasticity and elongation.
[0090] (Reference example 1) As shown in the formulation in Table 1, except that FA-310AH was used as component (A) and the amount of Percumyl D was 0.53 parts by mass, a thermosetting resin composition 1 was prepared in the same manner as in Experimental Example 1, a resin plate 1 was produced, and the phase separation structure was measured, and the phase separation structure was confirmed. Using a comma coater (manufactured by Hirano Tecseed Co., Ltd., "M-500"), the uncured thermosetting resin composition 1 was applied onto a release paper at a resin basis weight of 27 g / m 2 A resin film was produced by coating the resin film with a carbon fiber (TR 50S15L, manufactured by Mitsubishi Chemical Corporation) with a fiber weight of 125 g / m 2 The carbon fiber sheet was then wound using a drum winding device to obtain a sheet of 179 g / m2. Another resin film was then laminated to the carbon fiber sheet on the drum winding device. The carbon fiber sheet sandwiched between the two resin films was passed through a fusing press (Asahi Textile Machinery Co., Ltd., JR-600LTSW) under conditions of a temperature of 70°C, a pressure of 0.2 MPa, and a feed rate of 3 m / min, and the carbon fiber sheet was impregnated with uncured thermosetting resin composition 1, resulting in a prepreg basis weight of 179 g / m2. 2 Thus, a unidirectional prepreg with a resin content of 30% by mass was obtained. Eighteen sheets of the obtained prepreg were stacked with the carbon fibers in the same direction, and the temperature was raised to 130°C at 2°C / min under a pressure of 0.7 MPa in an autoclave, and the sheets were heat-cured at 130°C for 90 minutes to obtain a carbon fiber reinforced plastic panel. The cross section of the obtained carbon fiber reinforced plastic was mechanically polished to obtain a highly smooth mirror surface. The obtained smooth cross section was subjected to electronic dyeing by exposing it to OsO4 vapor for 16 hours, and then subjected to a conductive treatment. The backscattered electron image of the electronically dyed cross section was observed using a scanning electron microscope (JSM-7610F, manufactured by JEOL Ltd.) with an accelerating voltage set to 5 kV. It was confirmed that a phase separation structure similar to that of resin plate 1 had been formed inside the matrix resin between the carbon fibers. [Industrial Applicability]
[0091] By using the prepreg in the above-mentioned form, a fiber-reinforced plastic excellent in toughness and elastic modulus can be obtained. Therefore, according to the present invention, the fiber-reinforced plastic molded article having excellent mechanical properties can be widely applied from molded articles for sports and leisure such as fishing rods, golf shafts, and rackets to molded articles for industrial use such as aircraft and automobiles. [Explanation of symbols]
[0092] 1. Domain Y 2. Domain X 3 Ferret diameter
Claims
1. A prepreg comprising reinforcing fibers and a matrix resin, the matrix resin comprising an epoxy resin, a cured product obtained by curing the matrix resin under the following curing conditions has a sea-island phase-separated structure composed of domains X and Y, the domains X constitute island portions having a size R of 400 nm or less as measured by the following measurement method, and a ratio L / R of a distance L between the domains X to the size R is 1.1 or more. Curing conditions; The matrix resin is injected between two glass plates to form a plate having a thickness of 2 mm, and the oven atmosphere temperature is raised to 130° C. at a rate of 2° C. / min, and maintained at 130° C. for 90 minutes. Measurement conditions: As a pretreatment, a section having a thickness of 60 to 90 nm was cut from the cross section of the cured product using an ultramicrotome, and the obtained section was treated with RuO 4 Electron staining was performed by exposing the specimen to steam for 7 minutes. 4 From the cross section of the cured product exposed to steam for 16 hours, a section having a thickness of 60 to 90 nm is cut using an ultramicrotome. The phase separation structure of the section that has been pretreated and stained with electrons is observed using a transmission electron microscope (TEM) with an acceleration voltage set to 80 kV, and a TEM image is obtained. The obtained TEM image is smoothed and background subtracted using image analysis software, and the boundaries of the binarized image are detected. The size R is the median of the maximum Feret diameter of the domain X. The distance L between the domains X is the median of the distance from the center of gravity of the domain X to the center of gravity of the nearest other domain X.
2. 2. The prepreg according to claim 1, wherein the ratio L / R is 100 or less.
3. The prepreg according to claim 1 or 2, wherein the size R is 1 nm or more.
4. The prepreg according to any one of claims 1 to 3, wherein the matrix resin comprises the following components (A) and (B): Component (A): (meth)acrylate monomer Component (B): Hardener.
5. The prepreg according to claim 4 , wherein the component (A) comprises a monofunctional (meth)acrylate monomer.
6. The prepreg according to claim 4 or 5, wherein the component (A) comprises a polyfunctional (meth)acrylate monomer.
7. The prepreg according to any one of claims 1 to 6, wherein the domain X comprises a polymer of a (meth)acrylate monomer.
8. The prepreg according to any one of claims 1 to 7, wherein the domain Y comprises a cured product of an epoxy resin.
9. The prepreg according to any one of claims 4 to 8, wherein the component (B) comprises a component (b1) which is at least one selected from dicyandiamide, ureas, imidazoles, and aromatic amines.
10. The prepreg according to claim 9, wherein the component (b1) is contained in an amount of 1 to 15 parts by mass per 100 parts by mass of all epoxy resins contained in the matrix resin.
11. The prepreg according to any one of claims 4 to 10, wherein the component (B) comprises at least one component (b2) which is a radical polymerization initiator.
12. The prepreg according to claim 11, wherein the component (b2) is contained in an amount of 0.1 to 5 parts by mass relative to 100 parts by mass of the total matrix resin.
13. The prepreg according to claim 11 or 12, wherein the component (b2) includes a compound having a 10-hour half-life temperature of 70° C. or higher.
14. The prepreg according to any one of claims 11 to 13, wherein the component (b2) contains at least one peroxide-based compound selected from the group consisting of diacyl peroxides, alkyl peroxy esters, peroxydicarbonates, peroxyketals, dialkyl peroxides, and hydroperoxides.
15. The prepreg according to any one of claims 1 to 14, wherein the component (A) is contained in an amount of 5 to 45 parts by mass based on 100 parts by mass of the total epoxy resin.
16. The prepreg according to any one of claims 1 to 15, wherein the reinforcing fibers comprise carbon fibers.
17. A fiber reinforced plastic obtained by curing the prepreg according to any one of claims 1 to 16.
18. A fiber-reinforced plastic comprising reinforcing fibers and a matrix resin, the matrix resin having a sea-island phase-separated structure consisting of domains X and Y, the domains X constituting island portions having a size R of 400 nm or less as measured by the following measurement method, and a ratio L / R of a distance L between domains X to the size R being 1.1 or more. Measurement conditions: As a pretreatment, the cross section of the fiber-reinforced plastic is mechanically polished to obtain a mirror surface. 4 Steam and OsO 4 The cross section is exposed to steam for electron staining. After the conductive treatment, a scanning electron microscope (SEM) with an acceleration voltage set to 5 kV is used to obtain a backscattered electron image of the cross section that has been subjected to electron staining, and the phase separation structure is observed. The backscattered electron image obtained is smoothed and background subtracted using image analysis software, and the boundaries of the binarized image are detected. The size R is the median of the maximum Feret's diameter of the domain X. The distance L between the domains X is the median of the distance from the center of gravity of the domain X to the center of gravity of the nearest other domain X.
19. The fiber reinforced plastic according to claim 18, wherein the ratio L / R is 100 or less.
20. The fiber-reinforced plastic according to claim 18 or 19, wherein the size R is 1 nm or more.
21. The fiber reinforced plastic according to any one of claims 18 to 20, wherein the domain X comprises a polymer of a (meth)acrylate monomer.
22. The fiber reinforced plastic according to any one of claims 18 to 21, wherein the domain Y contains a cured product of an epoxy resin.
23. The fiber-reinforced plastic according to any one of claims 18 to 22, wherein the reinforcing fibers comprise carbon fibers.
24. The method for producing the prepreg according to any one of claims 1 to 16, comprising stacking and heating and pressurizing a film made of the matrix resin, thereby impregnating a reinforcing fiber base material containing the reinforcing fibers with the matrix resin. The method for producing a prepreg includes the steps of:
Citation Information
Patent Citations
Manufacture of prepreg andreinforced composite material
JP1985071640A
Manufacture of liquid resin suitable for composite structural filament winding
JP1985170618A
Curable resin composition, and film, molding, prepreg and fiber-reinforced plastic including the same
JP2019157056A
Epoxy resin composition, prepreg, and fiber-reinforced composite material
WO2008143044A1
Epoxy resin composition, prepreg, abd fiber-reinforced composite material
WO2009107697A1